Deep structural insights into the origin of the Heyuan ms 4.5 revealed by deep seismic sounding profiles in southeast China - Song, Jiajia; Wang, Shuaijun; Duan, Yonghong; Ye, Xiuwei; Lv, Zuoyong; Wang, Liang; Liu, Baofeng; Song, Xianghui; Cheng, Guoliang; Ruan, Mingming (Frontiers in Earth Science, 2024)
This study presents an interpretation of a deep seismic sounding (DSS) profile that carried out along the Cathaysia Block in southeast china, aiming to explore the crustal velocity structure. Data used in the survey were obtained from three controlled-source explosions conducted along the 320 km long Lianping-Heyuan-Shanwei profile. The modeling was based on ray tracing, using the extrapolation of seismic wave arrival times with the help of travel times predicted from a one-dimensional velocity model. The average velocity structure of the middle crust is 6.0–6.4 km/s, while a low velocity anomaly of approximately 0.1–0.2 km/s in the vicinity of the Heyuan-Shaowu fault zone. The resulting 2D velocity model indicates that steeply dipping low-velocity zones that correlate with the projection of two major fault zones. These zones, together with a flat LVZ at a depth of 12 km, define a triangular region that correlates with numerous hypocenters. This tectonic setting is favorable for the accumulation and release of strain in high-velocity media within the triangular region. The unique triangular structure in the upper crust provides necessary shallow medium conditions for seismic activity. This indicates that increased seismicity within this area is partially attributed to heightened stress within higher-velocity material. The triangular annular low-velocity body, situated in the upper crust, is influenced by dynamic environmental factors caused by deep thermal disturbances. The deep-seated fault serves as a conduit for the historical migration of thermal material, likely contributing to the seismogenic conditions for earthquakes in Heyuan’s region through deep-seated thermal disturbances. These findings provide a novel geophysical reference model for the regional seismicity near the Xinfengjang reservoir and significantly contribute to understanding the causal relationship between tectonic setting and seismicity. In comparison with previous studies, our research is dedicated to investigating the causes of shallow earthquakes in the region and exploring the relationship between deep and shallow structures.